2014
DOI: 10.11604/pamj.2014.19.87.4747
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycose pelvienne pseudo tumorale associée au dispositif intra-utérin: à propos de trois cas

Abstract: L'actinomycose est une maladie chronique suppurative granulomateuse d'origine infectieuse responsable d'un syndrome tumoral. La localisation pelvienne est rare et souvent associée, chez la femme, au port au long court du dispositif intra-utérin (DIU). Le diagnostic préopératoire n'est possible que dans 17% des cas. Nous rapportons trois observations, d'actinomycose pelvienne pseudo tumorale compliquées chez des femmes porteuses de DIU, qui illustrent le rôle de ce moyen de contraception dans la genèse de cette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The colonization rate increases with the duration of its maintenance. 2 , 5 Vasilesco et al 6 reviewed the medical records of 28 patients with abdominopelvic actinomycosis (9 men and 19 women) and the cause of actinomycosis in the studied group was an IUD device in 17 cases from which, 6 patients were admitted because they mimicked a complicated abdominopelvic malignant ovarian advanced ovarian cancer. To reduce the occurrence of this affection, it is recommended that IUDs be changed periodically, every 3–5 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The colonization rate increases with the duration of its maintenance. 2 , 5 Vasilesco et al 6 reviewed the medical records of 28 patients with abdominopelvic actinomycosis (9 men and 19 women) and the cause of actinomycosis in the studied group was an IUD device in 17 cases from which, 6 patients were admitted because they mimicked a complicated abdominopelvic malignant ovarian advanced ovarian cancer. To reduce the occurrence of this affection, it is recommended that IUDs be changed periodically, every 3–5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Such a pattern may be attributed to the proteolytic enzyme produced by A israelii . 2 Moreover, some investigators suggested that patients with elevated CRP, decreased hemoglobin, increased erythrocyte sedimentation rate, and slightly increased CA125 can have renal pelvis dilation or hydronephrosis. 7 Our patient presented anemia and elevated CRP with normal tumor marker and the CT scan had objectified the local urinary and digestive impact of actinomycosis resulting in hydronephrosis and colonic occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation

Pelvic actinomycosis secondary to intrauterine device.

Hernández-Alonso,
Ferrer Vilela,
Fernández del Castillo Ascanio
et al. 2023
Rev Esp Enferm Dig